Pemberdayaan Paguyuban Seni Langen Bekso Rahayu Ngremboko untuk Pembentukan Karakter dan Nilai Moral Anak Desa Sukorejo Kabupaten Pacitan - Wulan Trisnawaty; Esti Nur Qorimah; Samsul Hadi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to foster character development and moral values among children in Sukorejo Village in response to the challenges of digitalization that may negatively affect positive moral values. The program employed a Participatory Action Research (PAR) approach implemented through five stages: socialization, training, technology application, mentoring and evaluation, and program sustainability. The outcomes of the program resulted in two main outputs: an age-appropriate innovation of the Langen Bekso dance and the development of the Langen Bekso website as a digital information platform presenting the history, cultural values, and artistic activities of the Paguyuban Rahayu Ngremboko community. The simplification of dance movements facilitated children’s learning, fostered pride in local culture, and strengthened discipline and togetherness. In addition, regular psychosocial mentoring and moral education classes contributed to the development of positive character traits, such as honesty, responsibility, and empathy. Educational efforts and the rebranding of Langen Bekso also enhanced community understanding of the relevance of traditional arts in the modern era, thereby promoting the sustainable preservation of local culture.